STUDI PERBANDINGAN PENGATURAN PEMBERHENTIAN PRESIDEN DAN ATAU WAKIL PRESIDEN ANTARA INDONESIA DENGAN INDIA ATAS PERBUATAN TERCELA - Robert Reiman Simanullang; Mexsasai Indra; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In the constitutional system, there is an institution called impeachment. Manyparties understand that impeachment is the downfall, cessation, or dismissal ofthe President or high-ranking officials from office. In fact, the meaning ofimpeachment itself is an accusation or indictment so that impeachment focusesmore on the process and does not necessarily end with the cessation or removalof the President and other high-ranking state officials from office. Each countrythat has adopted the provisions on impeachment regulates these mattersdifferently, in accordance with the arrangements in the constitution. In Indonesia,there are grounds for impeachment of the President, one of which is misconduct,where there is still no clarity regarding the regulation of misconduct both in the1945 Constitution and other laws. Misconduct as a reason for impeachment ofthe President in Indonesia is still multi-interpreted, making it a rubber articlethat can be